(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
this article explores the integration of outsourcing services in food supply chains within national guard systems, drawing on experiences from advanced foreign militaries to inform potential reforms in Uzbekistan’s National Guard. By analyzing models from countries such as the United States, the United Kingdom, Germany, France, and others, the study highlights how outsourcing enhances efficiency, reduces costs, and improves nutritional quality while addressing challenges like quality control and dependency on private contractors. Ultimately, the research proposes tailored recommendations for Uzbekistan, emphasizing the adoption of hybrid outsourcing approaches that align with national security priorities and leverage international best practices to ensure resilient and sustainable food provisioning for military personnel.